Wear-resistant and corrosion-resistant nano multilayer ceramic-based thin film as well as preparation method and application thereof

By depositing a chromium transition layer and a tungsten diboride/carbon nano-multi-layer ceramic-based film on the surface of the transmission parts of amphibious armored vehicles, the problems of friction wear and corrosion in marine salt spray environments are solved, and the efficient wear and corrosion resistance of the parts are achieved, and the service life of the parts is extended.

CN119876854AActive Publication Date: 2025-04-25NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510147205.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-04-25
Estimated Expiration
2045-02-10

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the friction wear and corrosion problems of amphibious armored vehicle transmission components in marine salt spray environments, resulting in reduced component performance and increased operating costs.

Method used

The chromium transition layer is deposited by multi-arc ion plating technology, and the tungsten diboride/carbon nanolayer and carbon nanolayer are deposited successively on it through magnetron sputtering technology to form a nano-multi-layer ceramic base film to improve the wear and corrosion resistance of the components.

Benefits of technology

This nano-multi-layer ceramic-based film exhibits good tribological properties and wear resistance in both atmospheric and salt spray environments, significantly reducing the friction coefficient and wear rate of the transmission parts, and extending the service life and maintenance period of the parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876854A_ABST
    Figure CN119876854A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant and corrosion-resistant nano multilayer ceramic-based thin film as well as a preparation method and application of the wear-resistant and corrosion-resistant nano multilayer ceramic-based thin film. The wear-resistant and corrosion-resistant nano multilayer ceramic-based thin film comprises a chromium transition layer and a nano multilayer composite structure which are sequentially stacked in the thickness direction of the wear-resistant and corrosion-resistant nano multilayer ceramic-based thin film, the nano multilayer composite structure comprises a plurality of periodic units which are arranged in a stacked mode, and each periodic unit comprises a tungsten diboride / carbon nano layer and a carbon nano layer; the tungsten diboride / carbon nano layer in the periodic unit adjacent to the chromium transition layer is adjacent to the chromium transition layer, and the carbon nano layer is arranged at the top end of the nano multi-layer composite structure. The wear-resistant and corrosion-resistant nano-multilayer ceramic-based thin film is high in binding force, low in atmospheric environment friction coefficient, good in friction reduction performance and seawater corrosion resistance, capable of meeting the requirements for lubrication stability and long-life service of parts of a ship transmission system and capable of overcoming the defect that a carbon-based thin film is poor in salt spray resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface treatment, and in particular relates to a wear-resistant and corrosion-resistant nano multilayer ceramic-based film and a preparation method and application thereof. Background Art

[0002] Under the guidance of the goal of strengthening the army, the troops' actual combat training and exercise tasks have increased, the intensity has increased year by year, and the equipment has been used more and more frequently. It is particularly important to do a good job of equipment maintenance, especially for amphibious armored vehicles, because they often go to sea and are easily corroded by seawater, so maintenance work is even more important. The power components (transmission gears and shafts or other transmission mechanisms, etc.) of amphibious armored vehicles are generally not in direct contact with seawater. The salt mist caused by the evaporation of seawater at high temperature is very serious, and the surface of the transmission parts in contact with the air is in a more severe corrosion environment. For mechanical open motion systems / components that are in direct contact with the tropical marine atmosphere, the friction and wear problems are mainly solved by self-lubricating coating technology, and the corrosion problems are also mainly solved by insulating corrosion-resistant coating material technology. However, the actual working environment of amphibious equipment is a coupling of multiple damage conditions such as salt spray and wear. Therefore, the development of a new and efficient anti-friction, wear-resistant and corrosion-resistant film is of great significance for improving the performance of components and reducing operating costs.

[0003] Diamond-like carbon-based films have attracted much attention as solid lubricating materials due to their excellent properties such as high hardness, high wear resistance, and low friction coefficient. However, in the marine salt spray atmosphere, graphite easily absorbs water vapor or is oxidized by corrosive media into complex oxides, causing corrosion and a sharp deterioration in tribological properties. Tungsten diboride (WB2) film is a new type of superhard film with high hardness, high melting point, chemical inertness and thermal conductivity. WOx can be formed during the wear process, giving the film good self-lubrication. However, it was found during the research process that tungsten oxide is difficult to form a transfer film and adhere to the steel ball, resulting in the WB2 film still maintaining a high friction coefficient. Summary of the invention

[0004] The main purpose of the present invention is to provide a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film and a preparation method and application thereof, so as to overcome the shortcomings of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] One aspect of the present invention provides a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film, which comprises: a chromium transition layer and a nano-multilayer composite structure stacked in sequence in the thickness direction thereof, wherein the nano-multilayer composite structure comprises a plurality of periodic units stacked in layers, each periodic unit comprising a tungsten diboride / carbon (WB2 / C) nanolayer and a carbon nanolayer;

[0007] The tungsten diboride / carbon nanolayer in the periodic unit adjacent to the chromium transition layer is arranged adjacent to the chromium transition layer, and the top of the nano multilayer composite structure is the carbon nanolayer.

[0008] Another aspect of the present invention provides a method for preparing a wear-resistant and corrosion-resistant nano multilayer ceramic-based film, comprising:

[0009] A chromium transition layer is deposited on the substrate surface using multi-arc ion plating technology;

[0010] By using magnetron sputtering technology, tungsten diboride / carbon nanolayer and carbon nanolayer are sequentially deposited on the chromium transition layer to form a periodic unit. 100 periodic units are repeatedly prepared to obtain a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film.

[0011] Another aspect of the present invention provides a wear-resistant and corrosion-resistant nano multilayer ceramic-based film prepared by the preparation method.

[0012] Another aspect of the present invention provides the use of the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film in substrate protection, wherein the substrate includes at least a partial surface of a marine equipment transmission system or component.

[0013] Compared with the prior art, the present invention has at least the following beneficial effects:

[0014] The tungsten diboride / carbon nanolayer and the carbon nanolayer film prepared by the present invention adopt advanced materials, preparation technology and appropriate modulation ratio, and the synergistic effect of the two can induce tungsten oxide lubrication, have high bonding force, low friction coefficient in atmospheric environment, good friction reduction and wear reduction performance, and seawater corrosion resistance, can meet the requirements of lubrication stability and long service life of ship transmission system components, and make up for the disadvantage of poor salt spray resistance of carbon-based films. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 Schematic diagram of the structure of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 of the present invention;

[0017] Figure 2 is a cross-sectional SEM image of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 of the present invention;

[0018] Figure 3is a transmission image of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 of the present invention;

[0019] Figure 4 This is a bonding force test diagram of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film prepared in Example 3 of the present invention;

[0020] Figure 5 is a friction curve diagram of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 of the present invention under atmospheric friction;

[0021] Figure 6 The sample pictures of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 of the present invention after 7 days of salt spraying;

[0022] Figure 7 This is a graph of the average friction coefficient and wear rate of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 of the present invention after 7 days of salt spray friction. DETAILED DESCRIPTION

[0023] In view of the problems existing in the above-mentioned prior art, the inventors of the present invention have conducted extensive and in-depth research and provided a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film and a preparation method and application thereof, which is mainly designed through structural design, a nano-multilayer structure film is designed, and a tungsten diboride / carbon target and a carbon target are alternately cycled by adjusting the sputtering time of the carbon target, and a tungsten diboride / carbon nanolayer and a carbon nanolayer are deposited on the substrate surface to prepare a nano-multilayer film. The WB2 / C nano-multilayer film of the present invention can present excellent tribological properties in the atmosphere, reduce the friction coefficient of the A1B2 type WB2 film, and can still maintain good friction performance in a salt spray environment, making up for the disadvantage of the poor salt spray resistance of the carbon-based film.

[0024] The technical solution, its implementation process and principle will be further explained as follows.

[0025] As one aspect of the technical solution of the present invention, a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film is provided, comprising: a chromium transition layer and a nano-multilayer composite structure sequentially stacked in the thickness direction thereof, wherein the nano-multilayer composite structure comprises a plurality of stacked periodic units, each periodic unit comprising a tungsten diboride / carbon nanolayer and a carbon nanolayer;

[0026] The tungsten diboride / carbon nanolayer in the periodic unit adjacent to the chromium transition layer is arranged adjacent to the chromium transition layer, and the top of the nano multilayer composite structure is the carbon nanolayer.

[0027] In some embodiments, the nano-multilayer composite structure includes 100 periodic units.

[0028] In some embodiments, the nano multilayer composite structure includes tungsten diboride / carbon nanolayers and carbon nanolayers that are alternately stacked in sequence.

[0029] In some embodiments, the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film has a C atomic percentage of 65-80%, a W atomic percentage of 9-11%, and a B atomic percentage of 14-26%.

[0030] In some embodiments, the thickness of the chromium transition layer is 80-100 nm.

[0031] In some embodiments, the carbon nanolayer has a thickness of 5 to 8 nm.

[0032] In some embodiments, the thickness of the tungsten diboride / carbon nanolayer is 8-12 nm.

[0033] In some embodiments, the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film has a thickness of 1380 to 2100 nm.

[0034] In some embodiments, the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film has a bonding force of 28 to 30N.

[0035] In some embodiments, the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film has a friction coefficient of 0.2 to 0.28 and a wear rate of 2.91 to 4.21 x 10 -7 mm 3 / Nm.

[0036] In some embodiments, the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film has a friction coefficient of 0.25 to 0.35 and a wear rate of 10 to 16 x 10 -7 mm 3 / Nm.

[0037] As another aspect of the technical solution of the present invention, a method for preparing a wear-resistant and corrosion-resistant nano multilayer ceramic-based film is provided, comprising:

[0038] A chromium transition layer is deposited on the substrate surface using multi-arc ion plating technology;

[0039] By using magnetron sputtering technology, tungsten diboride / carbon nanolayer and carbon nanolayer are sequentially deposited on the chromium transition layer to form a periodic unit. 100 periodic units are repeatedly prepared to obtain a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film.

[0040] In some embodiments, the preparation method specifically includes: performing plasma etching treatment on the substrate; wherein the plasma etching treatment includes: applying a bias voltage of 180 to 220 V to the substrate, an etching time of 30 to 40 minutes, and an etching temperature of 200 to 300°C.

[0041] In some embodiments, the material of the substrate includes at least any one of 316 stainless steel or single crystal silicon wafer, but is not limited thereto.

[0042] In some embodiments, the preparation method specifically includes: using multi-arc ion plating technology, using a chromium target as a cathode target material, using an inert gas as a working gas, applying a target current to the chromium target, applying a negative bias voltage to the substrate, and depositing the chromium transition layer on the substrate surface;

[0043] Among them, the target current in the multi-arc ion plating technology is 20-30A, the bias voltage is 20-30V, the gas flow rate of the working gas is 350-400sccm, the deposition time is 480-500s, and the rotation speed is 1-3r / min; the inert gas includes argon.

[0044] In some embodiments, the preparation method specifically further comprises: using magnetron sputtering technology, using a tungsten diboride / carbon target as a cathode target material, using an inert gas as a working gas, applying a target current to the tungsten diboride / carbon target, and applying a negative bias voltage to the substrate, thereby depositing a tungsten diboride / carbon nanolayer on the chromium transition layer;

[0045] Among them, the target current in the magnetron sputtering technology is 40-60A, the power is 3-4kW, the gas flow rate of the working gas is 200-300sccm, the deposition time is 60-80s, and the rotation speed is 3-5r / min; the inert gas includes argon.

[0046] In some embodiments, the preparation method specifically includes: using magnetron sputtering technology, using a carbon target as a cathode target material, using an inert gas as a working gas, applying a target current to the carbon target, and applying a negative bias voltage to the substrate, thereby depositing a carbon nanolayer on the tungsten diboride / carbon nanolayer;

[0047] Among them, the target current in the magnetron sputtering technology is 40-60A, the power is 5-6kW, the gas flow rate of the working gas is 200-300sccm, the deposition time is 180-300s, and the rotation speed is 3-5r / min; the inert gas includes argon.

[0048] In some more specific embodiments, the preparation method may include the following steps:

[0049] (1) performing plasma etching on the substrate;

[0050] The plasma etching process includes: applying a bias voltage of 180-200V to the substrate, etching time of 30-40min, and etching temperature of 200-300°C.

[0051] (2) using multi-arc ion plating technology, using a chromium target as a cathode target material, using argon as a working gas, applying a target current to the chromium target, applying a negative bias voltage to the substrate, and depositing the chromium transition layer on the substrate surface;

[0052] Among them, the target current in the multi-arc ion plating technology is 20-30A, the bias voltage is 20-30V, the gas flow rate of the working gas is 350-400sccm, the deposition time is 480-500s, and the rotation speed is 1-3r / min.

[0053] (3) using magnetron sputtering technology, with a tungsten diboride / carbon target as a cathode target material, argon as a working gas, applying a target current to the tungsten diboride / carbon target, and applying a negative bias voltage to the substrate, thereby depositing a tungsten diboride / carbon nanolayer on the chromium transition layer;

[0054] The target current in the magnetron sputtering technology is 40-60A, the power is 3-4kW, the flow rate of the working gas is 200-300sccm, the deposition time is 60-80s, and the rotation speed is 3-5r / min.

[0055] (4) using magnetron sputtering technology, with a carbon target as a cathode target material, argon as a working gas, applying a target current to the carbon target, and applying a negative bias voltage to the substrate, thereby depositing a carbon nanolayer on the tungsten diboride / carbon nanolayer;

[0056] The target current in the magnetron sputtering technology is 40-60A, the power is 5-6kW, the flow rate of the working gas is 200-300sccm, the deposition time is 180-300s, and the rotation speed is 3-5r / min.

[0057] (5) Repeat steps 3 and 4 for 100 cycles to deposit a nano-multilayer composite film on the surface of the chromium transition layer.

[0058] As another aspect of the technical solution of the present invention, it also provides a wear-resistant and corrosion-resistant nano multilayer ceramic-based film prepared by the preparation method.

[0059] As another aspect of the technical solution of the present invention, it also provides the use of the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film in substrate protection, and the substrate includes at least a partial surface of a marine equipment transmission system or component.

[0060] Furthermore, the marine equipment includes ships.

[0061] In summary, the present invention deposits a nano multilayer film on the surface of a substrate by adjusting the sputtering time of a carbon target, setting an alternating cycle of tungsten diboride / carbon target and carbon target, and preparing a wear-resistant and corrosion-resistant nano multilayer ceramic-based film. The wear-resistant and corrosion-resistant nano multilayer ceramic-based film of the present invention can significantly reduce the friction coefficient of the surface of the transmission component, and also has excellent wear resistance and corrosion resistance, and can work stably for a long time in a harsh marine environment, greatly extending the service life and maintenance cycle of the transmission component.

[0062] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0063] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they can be obtained commercially. The commercial selection of the remaining raw materials and instruments not mentioned is all conventional selection and does not involve the core technical means of the present invention.

[0064] Example 1

[0065] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The wear-resistant and corrosion-resistant nano multilayer ceramic-based film is prepared on the substrate surface by magnetron sputtering technology, which mainly includes the following steps:

[0066] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0067] The cleaned substrate is placed in a vacuum chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4 mbar, pressure up to 3×10 -5 mbar. Sputtering cleaning target WB2 / C target (purity 99.9at.%, weight ratio 50:50) and C target. Preparation and deposition of wear-resistant and corrosion-resistant nano multilayer ceramic-based films, high-purity argon gas is filled into the cavity, and Cr target (purity 99.99at.%), WB2 / C target (purity 99.9at.%, weight ratio 50:50), C target (purity 99.99at.%) are used for control settings. The specific steps are as follows:

[0068] (1) Plasma etching, applying a bias voltage of 200 V to the substrate, the program running time is 40 min, and the chamber temperature is 300 °C;

[0069] (2) multi-arc ion plating chromium target, current 30.0A, bias voltage 20V, working gas Ar, gas flow rate 350sccm, deposition time 480s, rotation speed 2r / min to deposit a chromium transition layer on the substrate surface;

[0070] (3) Magnetron sputtering WB2 / C target, sputtering current 50.0A, power 4kW, working gas Ar, gas flow 200sccm, deposition time 60s, rotation speed 3r / min;

[0071] (4) Magnetron sputtering C target, sputtering current 50.0A, power 5kW, working gas Ar, gas flow rate 200sccm, deposition time 180s, rotation speed 3r / min;

[0072] (5) Repeat steps 3 and 4 for 100 cycles to deposit a nano-multilayer composite film on the surface of the chromium transition layer.

[0073] The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film is sample 1, and its specific composition parameters are shown in Table 1.

[0074] The sample 1 film obtained after the above deposition process was tested as follows:

[0075] (1) The film thickness was measured using a scanning electron microscope.

[0076] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0077] (3) A dry friction test was conducted at 25°C in an atmospheric environment using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr1 5 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0078] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear section was obtained by using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0079] Example 2

[0080] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The wear-resistant and corrosion-resistant nano multilayer ceramic-based film is prepared on the substrate surface by magnetron sputtering technology, which mainly includes the following steps:

[0081] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0082] The cleaned substrate is placed in a vacuum chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4 mbar, then keep the temperature at 160℃ and the pressure at 3×10 -5 mbar. Sputtering cleaning target WB2 / C target (purity 99.9at.%, weight ratio 50:50) and C target. Preparation and deposition of wear-resistant and corrosion-resistant nano multilayer ceramic-based films, high-purity argon gas is filled into the cavity, and Cr target (purity 99.99at.%), WB2 / C target (purity 99.9at.%, weight ratio 50:50), C target (purity 99.99at.%) are used for control settings. The specific steps are as follows:

[0083] (1) Plasma etching, applying a bias voltage of 200 V to the substrate, the program running time is 40 min, and the chamber temperature is 300 °C;

[0084] (2) multi-arc ion plating chromium target, current 30.0A, bias voltage 20V, working gas Ar, gas flow rate 350sccm, deposition time 480s, rotation speed 2r / min to deposit a chromium transition layer on the substrate surface;

[0085] (3) Magnetron sputtering WB2 / C target, sputtering current 50.0A, power 4kW, working gas Ar, gas flow rate 200sccm, deposition time 60s, rotation speed 3r / min;

[0086] (4) Magnetron sputtering C target, sputtering current 50.0A, power 5kW, working gas Ar, gas flow rate 200sccm, deposition time 240s, rotation speed 3r / min;

[0087] (5) Repeat steps 3 and 4 for 100 cycles to deposit a nano-multilayer composite film on the surface of the chromium transition layer.

[0088] The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film is sample 2, and its specific composition parameters are shown in Table 1.

[0089] The sample 2 film obtained after the above deposition process was tested as follows:

[0090] (1) The film thickness was measured using a scanning electron microscope.

[0091] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0092] (3) A dry friction test was conducted at 25 degrees using a friction tester (TRB3), and the test was repeated 2N3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0093] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear section was obtained by using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0094] Example 3

[0095] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The magnetron sputtering technology is used to prepare the W wear-resistant and corrosion-resistant nano multilayer ceramic-based film on the substrate surface, which mainly includes the following steps:

[0096] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0097] The cleaned substrate is placed in a vacuum chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4 mbar, then keep the temperature at 160℃ and the pressure at 3×10 -5 mbar. Sputtering and cleaning WB2 / C target (purity 99.9at.%, weight ratio 50:50) and C target. Preparation and deposition of wear-resistant and corrosion-resistant nano-multilayer ceramic-based films, high-purity argon gas is filled into the cavity, and Cr target (purity 99.99at.%), WB2 / C target (purity 99.9at.%, weight ratio 50:50), C target (purity 99.99at.%) are used for control settings. The specific steps are as follows:

[0098] (1) Plasma etching, applying a bias voltage of 200 V to the substrate, the program running time is 40 min, and the chamber temperature is 300 °C;

[0099] (2) multi-arc ion plating chromium target, current 30.0A, bias voltage 20V, working gas Ar, gas flow rate 350sccm, deposition time 480s, rotation speed 2r / min to deposit a chromium transition layer on the substrate surface;

[0100] (3) Magnetron sputtering WB2 / C target, sputtering current 50.0A, power 4kW, working gas Ar, gas flow rate 200sccm, deposition time 60s, rotation speed 3r / min;

[0101] (4) Magnetron sputtering C target, sputtering current 50.0A, power 5kW, working gas Ar, gas flow rate 200sccm, deposition time 300s, rotation speed 3r / min;

[0102] (5) Repeat steps 3 and 4 for 100 cycles to deposit a nano-multilayered film on the surface of the chromium transition layer.

[0103] The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film is sample 3, and its specific composition parameters are shown in Table 1.

[0104] The sample 3 film obtained after the above deposition process was tested as follows:

[0105] (1) The film thickness was measured using a scanning electron microscope.

[0106] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0107] (3) A dry friction test was conducted at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0108] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear section was obtained by using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0109] The cross-sectional SEM image of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film obtained in Example 3 is as follows: Figure 2 As shown, the transmission diagram is Figure 3 As shown in the figure, the bonding force morphology is as follows Figure 4 The friction curve of atmospheric friction is shown in Figure 5 As shown in Figure 2, the average friction coefficient and wear rate of the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film in a salt spray environment for 7 days are as follows: Figure 7 shown.

[0110] Comparative Example 1

[0111] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The wear-resistant and corrosion-resistant nano multilayer ceramic-based film is prepared on the substrate surface by magnetron sputtering technology, which mainly includes the following steps:

[0112] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0113] The cleaned substrate is placed in a vacuum chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4mbar, then keep the temperature at 160℃ and the pressure at 3×10 -5 mbar. Sputtering cleaning target WB2 / C target (purity 99.9at.%, weight ratio 50:50) and C target. Preparation and deposition of wear-resistant and corrosion-resistant nano multilayer ceramic-based films, high-purity argon gas is filled into the cavity, and Cr target (purity 99.99at.%), WB2 target (purity 99.9at.%), C target (purity 99.99at.%) are used for control settings. The specific steps are as follows:

[0114] (1) Plasma etching, applying a bias voltage of 200 V to the substrate, the program running time is 40 min, and the chamber temperature is 300 °C;

[0115] (2) multi-arc ion plating chromium target, current 30.0A, bias voltage 20V, working gas Ar, gas flow rate 350sccm, deposition time 480s, rotation speed 2r / min to deposit a chromium transition layer on the substrate surface;

[0116] (3) Magnetron sputtering of WB2 / C target, sputtering current of 50.0A, power of 4kW, working gas of Ar, gas flow of 200sccm, deposition time of 60s, rotation speed of 3r / min;

[0117] (4) Magnetron sputtering C target, sputtering current 50.0A, power 5kW, working gas Ar, gas flow rate 200sccm, deposition time 120s, rotation speed 3r / min;

[0118] (5) Repeat steps 3 and 4 for 100 cycles to deposit a nano-multilayer composite film on the surface of the chromium transition layer.

[0119] The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film is sample 4, and its specific composition parameters are shown in Table 1.

[0120] The sample 4 film obtained after the above deposition process was tested as follows:

[0121] (1) The film thickness was measured using a scanning electron microscope.

[0122] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0123] (3) A dry friction test was conducted at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0124] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear section was obtained by using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0125] Comparative Example 2

[0126] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The WB2 / C film is prepared on the substrate surface by magnetron sputtering technology, which mainly includes the following steps:

[0127] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0128] The cleaned substrate was placed in the magnetron sputtering chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4 mbar, then keep the temperature at 160℃ and the pressure at 3×10 -5 mbar. Adjust the target distance for 5 minutes, and then sputter and clean the target for 25 minutes. Prepare and deposit WB2 / C film, fill the chamber with high-purity argon, use Cr target (purity of 99.99at.%), WB2 / C target (purity of 99.9at.%, weight ratio of 50:50) layout setting, use magnetron sputtering technology, the specific steps are as follows:

[0129] (1) Plasma etching: a bias voltage of 200 V was applied to the substrate, the program running time was 40 min, and the chamber temperature was 300 °C.

[0130] (2) A multi-arc ion plating chromium target is used with a current of 50.0 A, a power of 5 kW, an Ar gas, a gas flow rate of 150 sccm, a deposition time of 900 s, and a rotation speed of 3 r / min to deposit a chromium transition layer on the substrate surface;

[0131] (3) The chromium target and the WB2 / C target were sputtered simultaneously, with a sputtering current of 50.0 A, a power of 5 kW and 4 kW respectively, an Ar working gas, a gas flow rate of 150 sccm, a deposition time of 900 s, and a rotation speed of 3 r / min;

[0132] (4) WB2 / C target sputtering current is 50.0A, power is 4kW, working gas is Ar and C2H2, gas flow rate is 200sccm and 0sccm respectively, deposition time is 9000s, rotation speed is 3r / min to deposit WB2 / C film on the surface of chromium transition layer;

[0133] The prepared tungsten diboride-based composite film is sample 5, and its specific composition parameters are shown in Table 1.

[0134] The film of sample 5 prepared after the above deposition treatment was subjected to the following tests:

[0135] (1) The film thickness was measured using a scanning electron microscope.

[0136] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0137] (3) A dry friction test was conducted at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0138] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25 degrees using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear section was obtained by using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0139] Comparative Example 3

[0140] In this embodiment, the substrate material is 316 steel or single crystal silicon wafer. The carbon film is prepared on the substrate surface by magnetron sputtering technology, which mainly includes the following steps:

[0141] The substrate surface was mechanically polished, and the substrate material was placed in an acetone solution for ultrasonic cleaning for 15 minutes, dried with nitrogen, placed in an anhydrous ethanol solution for ultrasonic cleaning for 15 minutes, and dried with nitrogen.

[0142] The cleaned substrate was placed in the magnetron sputtering chamber and evacuated to a vacuum degree of less than 6×10 -4 mbar, then heated to 180°C and pressure to 4×10 -4 mbar, then keep the temperature at 160℃ and the pressure at 3×10 -5 mbar. Adjust the target distance for 5 minutes, and then sputter and clean the target for 25 minutes. Prepare the deposited carbon composite film, fill the chamber with high-purity argon, use Cr target (purity of 99.99at.%), C target (purity of 99.9at.%, weight ratio of 50:50) layout setting, use magnetron sputtering technology, the specific steps are as follows:

[0143] (1) Plasma etching: a bias voltage of 200 V was applied to the substrate, the program running time was 40 min, and the chamber temperature was 300 °C.

[0144] (2) A multi-arc ion plating chromium target is used with a current of 50.0 A, a power of 5 kW, an Ar gas, a gas flow rate of 150 sccm, a deposition time of 900 s, and a rotation speed of 3 r / min to deposit a chromium transition layer on the substrate surface;

[0145] (3) magnetron sputtering C target, working gas is Ar and C2H2, gas flow rate is 200sccm, 75sccm, deposition time is 9000s, rotation speed is 3r / min to deposit C composite film on the surface of chromium transition layer;

[0146] The prepared C composite film is sample 6, and its specific composition parameters are shown in Table 1.

[0147] The sample 6 film obtained after the above deposition process was tested as follows:

[0148] (1) The film thickness was measured using a scanning electron microscope.

[0149] (2) The bonding performance of the film was tested using the Revetest scratch test system (CSM, Revetest). Three scratch tests were performed at different positions. The experimental conditions were loading speed: 3 mm / min, scratch length: 5 mm, and loading force: 100 N. The test results are shown in Table 2.

[0150] (3) A dry friction test was carried out at 25°C in an atmospheric environment using a friction tester (TRB3), and the test was repeated 2-3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 3.

[0151] (4) A dry friction test was conducted on the samples after 7 days of salt spray at 25°C using a friction tester (TRB3), and the test was repeated 2 to 3 times. A GCr15 steel ball was used as the counterpart, and a reciprocating method was adopted with a frequency of 5 Hz, a track length of 5 mm, a running distance of 180 m, and a normal load of 5 N. The wear cross section was obtained using a surface profiler (ASTQ), and the wear volume was obtained by multiplying it by the running step length. The wear volume was divided by the load and stroke to obtain the wear rate. The test results of the friction coefficient and wear rate are shown in Table 4.

[0152] Table 1 Composition parameters of the film samples obtained in Examples 1-3 and Comparative Examples 1-3

[0153]

[0154] It can be seen from Table 2 that the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film sample 3 obtained in Laboratory 3 has the best bonding force.

[0155] Table 2 Binding strength data of film samples obtained from Examples 1-3 and Comparative Examples 1-3

[0156]

[0157] The friction coefficients and wear rates of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 in the atmospheric environment are shown in Table 3. The wear-resistant and corrosion-resistant nano multilayer ceramic-based film sample 3 in Example 3 has the best friction coefficient and the best wear rate.

[0158] Table 3 Friction and wear of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 under atmospheric conditions

[0159]

[0160] The corrosion of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 in a salt spray environment for 7 days is as follows: Figure 6 As shown, sample 4 in comparative example 1 and sample 5 in comparative example 2 and samples 1-3 in embodiments 1-3 were not corroded, and the C film in comparative example 3 showed film peeling.

[0161] The friction coefficient and wear rate of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 in a salt spray environment for 7 days are shown in Table 4. On the basis that film samples 1-5 are not corroded, the wear-resistant and corrosion-resistant nano multilayer ceramic-based film sample 3 in Example 3 has the best friction coefficient and the best wear rate.

[0162] Table 4 Friction and wear of the film samples obtained in Examples 1-3 and Comparative Examples 1-3 under salt spray environment for 7 days

[0163]

[0164] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0165] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0166] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A wear-resistant and corrosion-resistant nano-multilayer ceramic-based film, characterized in that: It includes a chromium transition layer and a nano multilayer composite structure stacked in sequence in the thickness direction, wherein the nano multilayer composite structure includes a plurality of periodic units stacked in layers, each periodic unit including a tungsten diboride / carbon nanolayer and a carbon nanolayer; The tungsten diboride / carbon nanolayer in the periodic unit adjacent to the chromium transition layer is arranged adjacent to the chromium transition layer, and the top of the nano multilayer composite structure is the carbon nanolayer.

2. The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film according to claim 1, characterized in that: The nano multilayer composite structure includes 100 periodic units; And / or, the nano multilayer composite structure comprises tungsten diboride / carbon nanolayers and carbon nanolayers which are alternately stacked in sequence; And / or, the wear-resistant and corrosion-resistant nano multi-layer ceramic-based film has a C atomic percentage of 65-80%, a W atomic percentage of 9-11%, and a B atomic percentage of 14-26%; And / or, the thickness of the chromium transition layer is 80 to 100 nm; And / or, the thickness of the carbon nanolayer is 5 to 8 nm; and / or, the thickness of the tungsten diboride / carbon nanolayer is 8 to 12 nm; And / or, the wear-resistant and corrosion-resistant nano multilayer ceramic-based film has a thickness of 1380 to 2100 nm.

3. The wear-resistant and corrosion-resistant nano-multilayer ceramic-based film according to claim 1, characterized in that: The bonding force of the wear-resistant and corrosion-resistant nano multilayer ceramic-based film is 28 to 30N; And / or, the wear-resistant and corrosion-resistant nano multilayer ceramic-based film has a friction coefficient of 0.2 to 0.28 and a wear rate of 2.91 to 4.21 x 10 -7 mm 3 / Nm; And / or, the wear-resistant and corrosion-resistant nano multilayer ceramic-based film has a friction coefficient of 0.25 to 0.35 and a wear rate of 10 to 16 x 10 -7 mm 3 / Nm.

4. A method for preparing a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film, characterized in that: A chromium transition layer is deposited on the substrate surface using multi-arc ion plating technology; By using magnetron sputtering technology, tungsten diboride / carbon nanolayer and carbon nanolayer are sequentially deposited on the chromium transition layer to form a periodic unit. 100 periodic units are repeatedly prepared to obtain a wear-resistant and corrosion-resistant nano-multilayer ceramic-based film.

5. The preparation method according to claim 4, characterized in that: include: performing plasma etching on the substrate; The plasma etching process includes: applying a bias voltage of 180 to 220 V to the substrate, etching for 30 to 40 minutes, and etching at a temperature of 200 to 300° C.; And / or, the material of the substrate includes at least any one of 316 stainless steel or single crystal silicon wafer.

6. The preparation method according to claim 4, characterized in that: include: The multi-arc ion plating technology is adopted, a chromium target is used as a cathode target material, an inert gas is used as a working gas, a target current is applied to the chromium target, a negative bias voltage is applied to the substrate, and the chromium transition layer is deposited on the surface of the substrate; Among them, the target current in the multi-arc ion plating technology is 20-30A, the bias voltage is 20-30V, the gas flow rate of the working gas is 350-400sccm, the deposition time is 480-500s, and the rotation speed is 1-3r / min; the inert gas includes argon.

7. The preparation method according to claim 4, characterized in that: Also includes: The magnetron sputtering technology is adopted, a tungsten diboride / carbon target is used as a cathode target material, an inert gas is used as a working gas, a target current is applied to the tungsten diboride / carbon target, and a negative bias voltage is applied to the substrate, so as to deposit a tungsten diboride / carbon nanolayer on the chromium transition layer; Among them, the target current in the magnetron sputtering technology is 40-60A, the power is 3-4kW, the gas flow rate of the working gas is 200-300sccm, the deposition time is 60-80s, and the rotation speed is 3-5r / min; the inert gas includes argon.

8. The preparation method according to claim 4, characterized in that: include: The magnetron sputtering technology is adopted, a carbon target is used as a cathode target material, an inert gas is used as a working gas, a target current is applied to the carbon target, and a negative bias voltage is applied to the substrate, so as to deposit a carbon nanolayer on the tungsten diboride / carbon nanolayer; Among them, the target current in the magnetron sputtering technology is 40-60A, the power is 5-6kW, the gas flow rate of the working gas is 200-300sccm, the deposition time is 180s-300s, and the rotation speed is 3-5r / min; the inert gas includes argon.

9. A wear-resistant and corrosion-resistant nano multilayer ceramic-based film prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the wear-resistant and corrosion-resistant nano-multilayer ceramic-based film according to any one of claims 1 to 3 and 9 in substrate protection, wherein the substrate comprises at least a partial surface of a marine equipment transmission system or component; wherein: The marine equipment includes ships.

Citation Information

Patent Citations

  • Diamond-like composite coating and preparation method thereof

    CN106756820A

  • WB2 / WBC multilayer hard coating and preparation method and application thereof

    CN111962022A

  • Diboride composite coating as well as preparation method and application thereof

    CN112553580A

  • Periodic dispersion strengthened nano multilayer carbon-based film, and preparation method and application thereof

    CN116855906A

  • Molybdenum disulfide / tungsten diboride nano-composite multilayer film and preparation method and application thereof

    CN117187764A